(untitled) (Journal on Excellence in College Teaching, 2024)
Instructors’ ability to foster students’ disposition to engage in critical thinking (CT) is instrumental for CT growth. University students’ (N = 1,352) semester-long gains across specific dispositions were compared when taught by professors who had received zero, one, two, or three semesters of training in CT pedagogy. All groups experienced statistically significant improvement (p < .001), but only the three-semester group demonstrated practically significant results across the majority of subscales (η2 > .20). The authors’ recommendations include implementing long-term faculty development programs to provide regular training in CT pedagogy and teaching strategies for attitude formation, authentic learning, student self-efficacy, and student academic control.